Mechanisms in dominant parkinsonism; The toxic triangle of LRRK2, α-synuclein and tau - Taymans, Jean-Marc (Bioessays, 2010)
Parkinson’s disease (PD) is generally sporadic but a number of genetic diseases have parkinsonism as a clinical feature. Two dominant genes, α-synuclein and leucine rich repeat kinase 2 (LRRK2), are important for understanding inherited and sporadic PD. α-Synuclein is a major component of pathological inclusions termed Lewy bodies found in PD. LRRK2, is found in a significant proportion of PD cases. These two proteins may be linked as most LRRK2 PD cases have α-synuclein positive Lewy bodies. Mutations in both proteins are associated with toxic effects in model systems although mechanisms are unclear. LRRK2 is an intracellular signaling protein possessing both GTPase and kinase activities that may contribute to pathogenicity. A third protein, Tau, is implicated as a risk factor for PD. We discuss the potential relationship between these genes and suggest a model for PD pathogenesis where LRRK2 is upstream of pathogenic effects through alpha-synuclein, tau or both proteins.